How does early symptom change predict subsequent course of depressive symptoms during psychotherapy?. (21st October 2021) - Fuhr, Kristina; Werle, Dustin; Batra, Anil
Abstract : Objectives: Previous studies reported about the influence of early changes on treatment response. However, the question of whether early changes can predict the subsequent course of depressive symptoms during treatment with psychotherapy has not yet been clearly answered. We aimed to investigate whether symptom course in the first weeks at the level of individual session can predict the further symptom progression on a session to session level during psychotherapy treatment in patients with Major Depression (MD). Design: Monocentric randomized controlled trial with psychotherapeutic treatment either with cognitive‐behavioural therapy (CBT) or hypnotherapy (HT). The longitudinal course of weekly depressive symptoms during the six months treatment period was examined. Methods: In this RCT with 152 randomized patients suffering from current mild‐to‐moderate MD, depressive symptoms were assessed on a weekly basis during the 20 sessions' treatment with individual psychotherapy. We only included patients for which sufficient data for our analysis were available. Three different linear and quadratic mixed model analyses with random effects for each patient were tested: Early change was defined as the individual percentage symptom change during the first two, three, four and five weeks. Symptoms from session four, five, six and seven onward were predicted using different models, with early change added to the model in a final step. Calculating all models separately for CBT and HT lead to comparable results. Result: A slow symptom decrease after session four, five, six, seven onward to the end of the treatment was found. However, adding early change to the model, had no effect on the further symptom course in all models. Conclusion: Symptom changes at early stages of psychotherapy should not be considered as being predictive for further symptom course. Practitioner points: The individual early symptom change in a treatment with psychotherapy in the first two, three, four, or five weeks of treatment does not predict the subsequent symptom course from session four, five, six, or seven onward at a session to session level. Symptom changes at early stages of psychotherapy should not be considered as being predictive for further symptom course. We found a symptom reduction ranging from 3% to 16% in the first two, three, four, or five weeks. Treatment response between the first and last therapy session was found in 54.5%, the number of remitted patients (with PHQ‐9 scores < 5) was 44.7%. A small symptom improvement of between 0.21 and 0.42 points in the PHQ‐9 scores per week in later stages of psychotherapy is likely in all patients (with and without early symptom improvement).